Taking life and death seriously bioethics from Japan - Takahashi, Takao, 1948- (Advances in bioethics ;, 2005)
Full-scale Bioethics research began in America around 1970, a decade later America introduced it into Japan. More recently Japanese researchers have realised the growing necessity to evaluate Bioethics more objectively. The principles and policies concerning Bioethics differ between countries. In particular, considerable discrepancies have been occurring between Japanese medical practices and the principles of Bioethics originally imported from America. This has lead to the need for a close investigation into the Japanese approach to Bioethics. Despite this however, there are currently only a few researchers studying the Japanese approach to Bioethics. This interdisciplinary anthology uniquely provides a significant examination of the Bioethics from Japan by considering Japanese views from various aspects, such as life and death, dignity, family and care. The authors of this volume believe that in establishing their own approach to Bioethics each country will increase the practicality of this discipline and, by doing so, will aid the search for the universal elements in Bioethics. The members of the Kumamoto University Bioethics Research Group have published a number of books on Bioethics in Japan over the past decade and in doing so have been preparing for the production of this anthology. The contributors of this volume are both current and former faculty members at Kumamoto University; a well-known institute for Minamata Disease and the volume contains essays written specifically in relation to this area of research.